ANALISIS PERAN ZAKAT DALAM MENINGKATKAN KESEJAHTERAAN USAHA KECIL DAN MENENGAH DI KOMUNITAS MUSLIM DI KOTA MEDAN - Nanda Kurniawan Lubis; Yenni Samri Juliati Nasution (Adisam Publisher, 2025)
This research aims to analyze the role of zakat in improving the welfare of Small and Medium Enterprises (UKM) in the Muslim community in Medan City. Zakat, as a financial instrument in Islam, not only functions as a religious obligation but also has great potential in reducing poverty and social injustice. SMEs in Medan City, which are an important pillar in the local economy, often face challenges such as limited capital, limited market access, and low managerial skills. This research uses a qualitative approach with a case study method to explore how zakat can be optimized to provide a positive impact on the development of SMEs. Data was collected through in-depth interviews with zakat managers, zakat-receiving SMEs, and Islamic economic experts, as well as through analysis of related documents. The research results show that zakat plays a significant role in supporting SMEs by providing the necessary capital assistance, training and mentoring. Appropriate and effective distribution of zakat can increase the capacity of SMEs, expand market access, and improve the managerial skills of business actors. Factors that influence the effectiveness of zakat distribution include transparency and accountability of zakat management institutions, active participation from the community, and support from government policies.